Competence development of trainees performing short‐type single‐balloon enteroscopy‐assisted endoscopic retrograde cholangiopancreatography in patients with surgically altered anatomy. (6th June 2022) - Tanisaka, Yuki; Mizuide, Masafumi; Fujita, Akashi; Jinushi, Ryuhei; Ogawa, Tomoya; Katsuda, Hiromune; Saito, Yoichi; Miyaguchi, Kazuya; Mashimo, Yumi; Ryozawa, Shomei
Abstract: Objectives: This study aimed to evaluate the trainees' practice and learning curve in short‐type single‐balloon enteroscopy (short SBE)‐assisted endoscopic retrograde cholangiopancreatography (ERCP) for patients with surgically altered anatomy (SAA) and determine how to train these trainees. Methods: The data of short SBE‐assisted ERCP procedures between September 2011 and June 2021 were analyzed. Results: Three trainees and 180 cases were included in the analysis. Each trainee performed 60 cases between April 2016 and June 2021. The trainees' completion rate was 73.9% (95% confidence interval [CI], 66.8‐80.1%). Adverse events occurred in 5.0% of cases (95% CI, 2.3‐9.3%). The trainee who experienced colonoscopy and ERCP the most achieved better outcomes of enteroscopy success (reaching the target site) and trainee's completion rates than those of the others ( P = .03 and .02, respectively). The learning curve for trainee's completion showed a significant improvement after 60 cases ( P = .001). Multiple logistic regression analysis indicated that Roux‐en‐Y reconstruction was the factor affecting trainees' completion failure. Conclusions: Short SBE‐assisted ERCP trainees has a substantial learning curve. If trainees do not have much experience with colonoscopy and ERCP procedures, it may be beneficial for them to start performing short SBE‐assisted ERCP procedures on non‐Roux‐en‐Y reconstruction cases. Abstract : Evaluation of trainees' practice and learning curves in short‐type single‐balloon enteroscopy‐assisted ERCP for patients with surgically altered anatomy revealed that trainees' successful completion rates significantly improved after 60 cases. Tanisaka et al. conclude that short‐type single‐balloon enteroscopy‐assisted ERCP poses a substantial learning curve for trainees.